Rapid Detection of Rifampin Resistance in Mycobacterium tuberculosis Isolates from India and Mexico by a Molecular Beacon Assay - Varma-Basil, Mandira (American Society for Microbiology, 2004)
We assessed the performance of a rapid, single-well, real-time PCR assay for the detection of rifampin-resistant Mycobacterium tuberculosis by using clinical isolates from north India and Mexico, regions with a high incidence of tuberculosis. The assay uses five differently colored molecular beacons to determine if a short region of the M. tuberculosis rpoB gene contains mutations that predict rifampin resistance in most isolates. Until now, the assay had not been sufficiently tested on samples from countries with a high incidence of tuberculosis. In the present study, the assay detected mutations in 16 out of 16 rifampin-resistant isolates from north India (100%) and in 55 of 64 rifampin-resistant isolates from Mexico (86%) compared to results with standard susceptibility testing. The assay did not detect mutations (a finding predictive of rifampin susceptibility) in 37 out of 37 rifampin-susceptible isolates from India (100%) and 125 out of 126 rifampin-susceptible isolates from Mexico (99%). DNA sequencing revealed that none of the nine rifampin-resistant isolates from Mexico, which were misidentified as rifampin susceptible by the molecular beacon assay, contained a mutation in the region targeted by the molecular beacons. The one rifampin-susceptible isolate from Mexico that appeared to be rifampin resistant by the molecular beacon assay contained an S531W mutation, which is usually associated with rifampin resistance. Of the rifampin-resistant isolates that were correctly identified in the molecular beacon assay, one contained a novel L530A mutation and another contained a novel deletion between codons 511 and 514. Overall, the molecular beacon assay appears to have sufficient sensitivity (89%) and specificity (99%) for use in countries with a high prevalence of tuberculosis.